Madurese Deverbal Nominalization Process - Hidayati, Alfin Fuji; Nurhayani, Ika; Choyimah, Nurul (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2021)
Nominalizations can be structured by adding affixes before or after root to create new words in language.  Madurese has several language aspects that have not been widely explored. Previous linguistic studies on Madurese mostly focused on morphological aspects such as Madurese affixation in general. Therefore, this research discusses Madurese Deverbal Nominalization Process (Noun Derived from Verb). The goals of this research are to identify what types of affixes which form deverbal nouns in Madurese and to know how the affixation process that forms the deverbal nouns in Madurese. For example: pa-mandi-an, the root is mandi (take a shower) after it attachés to confix (pa- -an) the word class category changes to noun pa-mandi-an, that is a bath room. This research is a descriptive qualitative research, and the data were collected from a Madurese short story entitled Tora (satengkes carpan Madura), which was written by Jamal D. Rahma (2017). The findings are presented descriptively by identifying the process of the derivational forming nouns. The results of this research shows that prefixes, suffixes, confixes and infixes are contributed to create new lexemes in Madurese.